Nutritional status and job performance of anganwadi workers - Shunmukhapriya S (Department of Home Science, College of Agriculture, 2005)
A study on “Nutritional status and job performance of anganwadi workers” was carried out to assess the nutritional status and job performance of anganwadi workers and to find out the relationship between nutritional status and job performance. Data regarding the socio-economic characteristics, job characteristics, food consumption pattern, energy balance, morbidity pattern, job performance and nutritional status of AWWs were studied in detail. From the present study it was found that 43.33 per cent of the AWWs belonged to the age group of 40-50 years and 56.67 per cent of the AWWs were educated up to high school. Social status of the AWWs indicated that 68.33 per cent of them were Hindus and 57.5 per cent belonged to other back ward classes. Seventy eight per cent of the AWWs were married. Fifty one per cent of the AWWs were members of an organization. Nuclear type of families of with four members is common among the surveyed AWWs. Economic status of the AWWs revealed that the mean income of the AWWs from their job was Rs.1363/- per month only and sixty per cent of the AWWs had family income less than Rs.3000. Forty per cent of the AWWs resided in rural areas and had a walk able distance of less than 1 kilometer from the center. Seventy five per cent of the AWWs of the present study had an experience of more than 20 years and had received refresher training 1-5 times and 19.17 per cent of the AWWs received refresher training 6-10 times. All the AWWs of the current study were habitual non-vegetarians. Frequency of use of cereals, other vegetables, fats and oils, nuts and oilseeds, and spices and condiments were daily in the dietaries while egg, meat and baked foods were less frequently used by the AWWs. On analyzing the energy balance of the AWWs it was found that 70 per cent of them were in positive energy balance. On analyzing the anthropometric data, it was found that more than fifty per cent of the AWWs had BMI and MUAC above normal and WHR of all the AWWs were above normal. Actual food intake of the AWWs assessed revealed that intake of food items like green leafy vegetables, milk and milk products as well as fruits were found to be below the RDA where as all the other food items were adequately met by the AWWs. With regard to nutrient intake carotene, iron and riboflavin were inadequate and the rest of the nutrients were adequately met when compared with RDA. Clinical examination of the AWWs revealed symptoms of mild forms of anaemia, dental caries, oedema and vision disorder. Fifty per cent of the AWWs surveyed had high blood pressure. Assessment of the biochemical parameter, haemoglobin level, indicated that 78.33 per cent of the AWWs were suffering from severe to mild forms of anaemia. With regard to morbidity pattern minor ailments like cold, headache, throat pain, cough and fever were reported among majority of the AWWs and it was also seen that 75 per cent of the AWWs had not availed any leave from work for the past six months. Nutritional status index of the AWWs ranged from –3.05 to 15.53 and medium nutritional status index was observed among 63.33 per cent of the AWWs and 18.33 per cent of the AWWs had high nutritional status index. Mean job performance scores of the AWWs ranged between 41.5 and 83.5. Of the 120 AWWs, 61.67 per cent had medium job performance scores and 18.33 per cent of the AWWs had high job performance scores. Self rating of job performance by the AWWs ranged between 21 to 57 .It was found from the study that 73.34 per cent of the AWWs rated themselves to have medium job performance and 13.33 per cent rated as having high job performance A positive and significant correlation was observed between nutritional status index with independent variables like family size, total family income, energy expenditure, energy balance and iron intake. A significant positive correlation was found between job characteristics like experience and number of refresher trainings attended with mean job performance scores as well as self-rating of job performance by AWWs. Dietary variables like calorie intake and iron intake were found to have significant positive correlation with mean job performance scores. A positive and significant correlation was seen between nutritional status index and the job performance rated by CDPOs and the self-rating by AWWs.